Diagnostic biomarkers for lung cancer prevention. (6th February 2018) - Gasparri, Roberto; Romano, Rosalia; Sedda, Giulia; Borri, Alessandro; Petrella, Francesco; Galetta, Domenico; Casiraghi, Monica; Spaggiari, Lorenzo
Abstract: Lung cancer is the leading cause of death for neoplasm. Lung cancer mortality is frequently associated with late diagnosis, therefore an early diagnosis is a key factor to significantly improve overall survival in high risk populations of asymptomatic patients. Conventional cancer screenings (low-dose computed tomography or chest x-ray) today offer early detection but are invasive and expensive. Previously these studies evaluated the solid and topographic cancer structure and morphology. Today the concept of tumor has been remodelled, being defined as a disease that has its own genetic, biological and metabolic identity; it is on this new awareness that we should base new screening methods. Recent research has shown great reliability of new tests such as exhaled breath analysis, serum biomarkers and urine analysis in early diagnosis of lung cancer. Analysis of new biomarkers associated with the high specificity of these new screening methods, which are non-invasive, safe, inexpensive and simple to perform, could allow a non-invasive approach to determine a big change in the early diagnosis of cancer and its survival rate. Furthermore, these new techniques put the patient at the core of a non-invasive diagnostic process and ensure a better quality of life during medical diagnosis. In this article, we want to analyze the possible benefits of these new and promising methods, suggesting a possible combination between them to ensure, as soon as possible, an early and effective diagnosis of lung cancer with a special focus on the patient, in a new era of personalized medicine.